Avaliação da atividade antifúngica in vitro e in vivo de derivados de chalconas e da tiossemicarbazona do lapachol contra isolados do gênero Paracoccidioides - Nívea Pereira de Sá (2013)
Paracoccidioidomycosis (PCM) is a systemic granulomatous disease caused by thermo-dimorphic fungus Paracoccidioides brasiliensis. This disease is limited to Latin American countries where it is recognized as the most prevalent systemic mycosis. The treatment of PCM is generally extended, and in many cases by one or two years or more; absence of the therapy is almost always fateful. Amphotericin B, sulfonamides, and azoles may be used in the treatment of PCM. Amphotericin B has been associated with high toxicity, which may hamper the treatment of severe infections. The prolonged course of treatment with azoles is a limiting factor. The sulfonamides were the first class of drugs of choice for the treatment of PCM, but the long treatment period, toxicity and cost of the therapy disadvantage its use. This leads to the need for new, safe and effective antifungal compounds for the treatment of PCM. In this context, the search for new compounds with activity against P. brasiliensis that have low toxicity and low cost is paramount. Molecules derived from chalcones and lapachol thiosemicarbazone (TSC) has demonstrated significant activity in vitro and in vivo against the fungus P. brasiliensis. From this, we performed tests with substances 3b, 4c, 3e, 4e and TSC to determine the inhibitory concentration and minimum fungicidal, check interaction with amphotericin, itraconazole and trimethoprim-ulfamethoxazole, and analysis by scanning electron microscopy and transmission the isolated Pb18 under treatment with these substances. Assays were performed with cell wall sorbitol, with markers of cell death DAPI and propidium iodide (PI) assays and phagocytosis of murine macrophages treated with these substances. The in vivo study of substances 4c and 4e were performed in BALB / c mice infected with isolate Pb18. After 15 days of infection the animals were treated with the substances at a dose of 5 mg / kg / day for 15 days. In this study we found that the substances were active against different isolates representing the phylogenetic species of the genus Paracoccidioides, and 4c showed synergistic interaction with itraconazole against the isolate Pb18. All substances caused morphological changes in the cell isolated from the Pb18 which in comparison with the markers of cell death DAPI and PI provide indications of processes of apoptosis and necrosis. However, none of the substances caused direct damage on the fungal cell wall. Substances 3b, 4c and 4e were able to increase the phagocytic index and fungicidal activity of murine macrophages in vitro. The substances 4c and 4e showed similar activity in vivo to itraconazole dose of 5 mg/kg/day, verified from the ability to reduce the number of CFU recovered from lung and facilitate the development of a Th1 4 immune response. However, just 4c showed histopathological features similar to itraconazole observed in the lung, liver and spleen, while the 4e showed the lung and liver more compromised by infection similar to the control group that received no treatment. Thus, the results presented in this study confirmed the potential of antifungal substances 3b, 4c, 3e, 4e and TSC presenting them as possible candidates for treatment of PCM.